Analisis Fraktal untuk Pengembangan Motif Batik Indonesia: Perpaduan Fisika dan Budaya - Kumala, Siti Ayu; Nur Huda, Didik; Nengsih, Retno (Jurusan Fisika, Universitas Bangka Belitung, 2025)
Batik as part of the Indonesian culture was recognized as an Intangible Cultural Heritage by UNESCO in 2009. Batik is not only a cultural product, but also a representation of a complex visual structure. As science and technology develop, a physico-mathematical approach to batik motifs, particularly through fractal theory, has begun to attract the attention of researchers. A fractal is a geometric shape that has a repeating pattern at various scales. This study aims to develop a fractal pattern using the Julia set to obtain a batik motif pattern. This will greatly assist the batik industry in producing batik with various motifs automatically. The method used is to modify the Julia equation, the next step is to perform a transformation in the form of rotation or dilation. Then the results obtained are visualized using Python programming. The constants used are varied with a value of -1 < c < 1, the order of the equation also uses a higher order. The visualization results are then compared with existing batik motifs and the best one is selected. The results showed that certain parameter modifications produced fractal patterns similar to traditional designs such as kawung batik, while others revealed unexpected analogies to natural and physical phenomena like dicotyledonous and monocotyledonous stems patterns and floral motifs.